DINITROGEN FIXATION IN THE WORLD'S OCEANS - Karl D.; Michaels A.; Bergman B.; Capone D.; Carpenter E.; Letelier R.; Lipschultz F.; Paerl H.; Sigman D.; Stal L. (My University, 2002)
The surface water of the marine environment has traditionally been viewed as a nitrogen (N) limited habitat, and this has guided the development of conceptual biogeochemical models focusing largely on the reservoir of nitrate as the critical source of N to sustain primary productivity. However, selected groups of Bacteria, including cyanobacteria, and Archaea can utilize dinitrogen (N2) as an alternative N source. In the marine environment, these microorganisms can have profound effects on net community production processes and can impact the coupling of C-N-P cycles as well as the net oceanic sequestration of atmospheric carbon dioxide. As one component of an integrated `Nitrogen Transport and Transformations' project, we have begun to re-assess our understanding of (1) the biotic sources and rates of N2 fixation in the world's oceans, (2) the major controls on rates of oceanic N2 fixation, (3) the significance of this N2 fixation for the global carbon cycle and (4) the role of human activities in the alteration of oceanic N2 fixation. Preliminary results indicate that rates of N2 fixation, especially in subtropical and tropical open ocean habitats, have a major role in the global marine N budget. Iron (Fe) bioavailability appears to be an important control and is, therefore, critical in extrapolation to global rates of N2 fixation. Anthropogenic perturbations may alter N2 fixation in coastal environments through habitat destruction and eutrophication, and open ocean N2 fixation may be enhanced by warming and increased stratification of the upper water column. Global anthropogenic and climatic changes may also affect N2 fixation rates, for example by altering dust inputs (i.e. Fe) or by expansion of subtropical boundaries. Some recent estimates of global ocean N2 fixation are in the range of 100-200 Tg N (1-2 × 1014 g N) yr-1, but have large uncertainties. These estimates are nearly an order of magnitude greater than historical, pre-1980 estimates, but approach modern estimates of oceanic denitrification.
Keywords: BACTERIA; BIOGEOCHEMISTRY; CLIMATE; CYANOBACTERIA; IRON; NITROGEN; OCEANIC N2 FIXATION; PHOSPHORUS; TRICHODESMIUM